Ethical issues in six religious traditions - Morgan, Peggy (Religious studies teacher); Lawton, Clive (Edinburgh University Press, 2007)
How do Hindus view euthanasia? Is there a 'Sikh view' of advertising? Do Jews and Muslims share the same attitude to marriage? How do Christian and Buddhist views on the environment differ? This book draws together authors respected in six traditions to explore in parallel the ethical foundations for Hindu, Buddhist, Sikh, Jewish, Christian and Muslim faiths. Each section introduces a different religion and asks specific, topical questions, set in a wider context. The issues addressed are religious identity and authority; the personal and the private; marriage and family; influences on and use of time, money and other personal resources; the quality and value of life; questions of right and wrong; equality and difference; conflict and violence and global issues. The contributors to this expanded edition are Peggy Morgan, Clive Lawton, Werner Menski, Eleanor Nesbitt, Alan Brown and Azim Nanji. Additions for this new edition include subsections on reproduction, vegetarianism, just war and terrorism, and genetic modification. The book is structured so that topics can be explored within a specific tradition or comparatively across the traditions.